Delineation of molecular characteristics in pediatric PFA ependymoma involving rare osseous and pulmonary metastases: A case report and literature review - Zhou, Mading; Wang, Leiming; Sun, Peng; Liu, Yutong; Chen, Ge; Zeng, Gao (Frontiers in Oncology, 2022)
Ependymoma is the third most common pediatric primary brain tumor, with its most aggressive subtype being posterior fossa group A (PFA). Extraneural metastasis of pediatric PFA ependymoma is rare. Herein, we present a case of a 9-year-old girl with PFA ependymoma characterized by a lack of trimethylation of histone H3 at lysine 27 and elevated chromosome X open reading frame 67 expression. Despite multiple surgeries and radiotherapies, the patient had a rapid recurrence and developed osseous and pulmonary metastases, which may be attributed to the homozygous deletion of cyclin-dependent kinase (CDK) inhibitor 2A/B and CDK12 mutation. Importantly, the CDK12 mutation observed in the patient may be indicative of the need for further work-up to consider chemotherapy rather than administering poly (adenosine diphosphate-ribose) polymerase inhibitors. Taken together, this is the first report of pediatric PFA ependymoma with extraneural metastases, wherein we clarified the diagnostic procedures of this newly identified PFA ependymoma and provided new cues to study the invasiveness of this disease and treatment selection for such patients.